2008
DOI: 10.1073/pnas.0807146105
|View full text |Cite
|
Sign up to set email alerts
|

Sustained induction of epithelial to mesenchymal transition activates DNA methylation of genes silenced in basal-like breast cancers

Abstract: The active acquisition of epigenetic changes is a poorly understood but important process in development, differentiation, and disease. Our work has shown that repression of the p16/pRb pathway in human epithelial cells, a condition common to stem cells and many tumor cells, induces dynamic epigenetic remodeling resulting in the targeted methylation of a selected group of CpG islands. We hypothesized that cells in this epigenetically plastic state could be programmed by the microenvironment to acquire epigenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
172
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(184 citation statements)
references
References 29 publications
5
172
1
1
Order By: Relevance
“…Otherwise, Dumont et al [41] proposed that DNA methylation profiles observed in BC may reflect the history of environmental exposures based on the induction of p16/Rb pathway and impact on epigenetic changes resulting from methylation of CpG islands associated with tumorigenesis [36,41]. Elsheik et al…”
Section: Epigenetic Changes Of Blbcmentioning
confidence: 99%
“…Otherwise, Dumont et al [41] proposed that DNA methylation profiles observed in BC may reflect the history of environmental exposures based on the induction of p16/Rb pathway and impact on epigenetic changes resulting from methylation of CpG islands associated with tumorigenesis [36,41]. Elsheik et al…”
Section: Epigenetic Changes Of Blbcmentioning
confidence: 99%
“…68 In the same line, Hu applied a methylation-specific digital karyotyping technique to epithelial and myoepithelial cells and stromal fibroblasts from normal breast tissue and from in situ and invasive breast carcinomas. 69 He found distinct epigenetic alterations in all three cell types during breast tumorigenesis in a tumor stage-and cell type-specific manner, suggesting that epigenetic changes play a role in maintaining the abnormal cellular microenvironment in breast cancer.…”
Section: Epigenetic Control Of Tumor Developmentmentioning
confidence: 99%
“…Ninety percent of patient deaths in solid tumors are due to metastasis, therefore, an understanding of the process and pathogenesis at the systemic, cellular and molecular levels is one of the most ambitious goals in cancer research (Gupta and Massague, 2006;Esteller, 2007). Epigenetic changes in the promoters of classical and small non-coding (miRNA) genes has a pivotal role in the acquisition of tumorigenic and metastatic properties (Feinberg and Tycko, 2004;Dumont et al, 2008;Lujambio et al, 2008). Methylation occurs in specific genomic areas called CpG islands, especially within the promoter region of a gene, thereby preventing gene expression (Weber et al, 2007).…”
Section: Introductionmentioning
confidence: 99%